Modified cascaded H-bridge multilevel inverter using particle swarm optimization - Al-Hiealy, Mohammed Rasheed Jubair (2018)
For more than two decades,multilevel inverters in different topologies and control strategies have been involved in many applications. In contrast to conventional three-level inverters, they are more efficient and better suited for applications requiring high power and high voltage levels. The current multilevel inverter topologies available in the market include diode clamped or neutral point clamped (NPC), capacitor clamped or flying capacitor (FC), and cascaded H-bridge (CHB). It is essential to produce an effective power converter from the perspective of cost, efficiency and output quality. These factors have lead to develop a new family of multilevel inverters known as modified CHB-MLIs of a single and three phases for five, nine and thirteen levels. This topology of the modified inverters requires fewer components compared to existing inverters (particularly in the higher levels) and requires fewer carrier signals and gate drives. Therefore,the overall cost and complexity are greatly reduced, particularly for higher output voltage levels. An important issue in the power electronic converters is the modulation control method in order to produce high quality output with a minimum distortion. As there exist many strategies for modulation, still the low-switching frequency technique is widely accepted in higher power applications. There are different optimization aims for different applications utilizing the low-switching frequency technique it is possible to increase the number of output voltage levels and produce a better sinusoidal output waveform and efficiency. The modified CHB-MLIs for five, nine and thirteen levels have a reduced number of DC power supplies and switches when compared to the conventional CHB topologies designed for the same number of voltage levels. The aim of this thesis is to investigate the performance of modified CHB-MLIs of a single and three phases for five, nine and thirteen levels based on cascaded multilevel inverter using low-switching frequency modulation scheme. The modulation method for obtaining the optimum switching angles based on Newton Raphson (NR) and Particle Swarm Optimization (PSO)control techniques have been proposed.A NR and PSO control techniques were presented for selective harmonics elimination (SHE) solution in a modified CHB-MLIs. These control techniques have been implemented through closed-loop control system using DSP TMS320F2812. In this thesis, the complete switching angles of the SHE has been developed by using a heuristic optimization technique namely PSO by solving the non-linear equation of the output voltage waveform and later validated with the conventional method NR. To validity of a low power prototype of the modified CHB-MLIs have been designed and implemented; analytical,simulation,and experimental results have been provided. The relative merits of the proposed modulation scheme based on the NR and PSO have been assessed based on modified inverters output quality and efficiency.Investigations of the proposed modulation scheme based on PSO have been revealed that the switching pattern of the adopted inverters has the capability of producing output voltage with minimal THD and high efficiency of the modified inverters. The results acquired from the simulation results the superiority of PSO over the conventional methods NR, where the THD reduction values in the three developed CHB-MLI namely five-level, nine level,and thirteen level are 15%,7.8%,and 5.2%, respectively.